МОНГОЛ УЛСЫН ТӨСВИЙН ХӨРӨНГӨ ОРУУЛАЛТЫН ҮР АШГИЙН СУДАЛГАА - Оюунцэцэг, Д (Proceedings of the Mongolian Academy of Sciences, 2016)
In brief, the legislations and purposes of the budget investment policy of Mongolia have been taken into account in this survey. The budget investment growth, total budget expenditure and the changes of the density to GDP since 1990 on dynamic growth method have been studied by using the official sources like National Statistical Office of Mongolia and the Ministry of Finance. Moreover, I summarized the budget investment efficiency by using the Incremental Capital-Output Ratio method (hereinafter referred to as ICOR) and data of the National Statistical Office of Mongolia from 2002 to 2012. GDP and investment indicators are computed at 2005 constant prices. Investment at current prices was multiplied with the deflator of the year 2005 to convert to at 2005 constant prices. Although, as the result of the analysis, the amount of budget investment cost and its density to GDP and state budget expenditure are increasing, investment budget is still not efficient enough. Accordingly, it is recommended to increase the budget investment benefit and to sophisticate its composition.